(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The aim of this work is to demonstrate that the summons at a specific time in Brazilian criminal proceedings process represents a legislative advance and it is justifiable to extend it to summonses as well, given the the common reasons behind it.